تطبيق وسيلة بطاقة الومضية في تعليم اللغة العربية لتنمية مهارة الكتابة الطلاب الصف السابع في المدرسة المتوسطة الإسلامية الأهلية "بحر العلوم" غنوكواتو جو مبانج - نور فضيلة; إسنية النسوة الماجستير (Al-Tadris: Jurnal Pendidikan Bahasa Arab, 2023)
In reality, the use of educational media as a teaching and learning technique is very necessary, because with new things in the learning process, students will feel involved and called upon to be able to overcome and solve learning problems without any pressure. The purpose of this study was to find out the steps for implementing flashcard media in learning Arabic to improve writing skills. In this study using descriptive qualitative research type. Data collection techniques used, first with observation then conducted interviews and continued with documentation. As for the data analysis technique in this study, namely data reduction, data presentation and drawing conclusions, and equipped with checking the validity of the data with the triagulation technique. Furthermore, the results of the study showed that the implementation of flash card media in learning Arabic to improve writing skills in class VII MTs Bahrul Ulum Genukwatu Jombang went well. The implementation of the flashcard media was by means of the teacher giving pictures and symbols to each group and then each group make sentences with the perfect number according to the pictures and symbols that have been shared by the teacher, in practice the teacher tries to use flash cards more often as a learning medium, this is because the student's response is very good as evidenced by the increase in student learning outcomes after using it flash cards as learning media.